1999
DOI: 10.1242/jcs.112.20.3421
|View full text |Cite
|
Sign up to set email alerts
|

Control of morphology, cytoskeleton and migration by syndecan-4

Abstract: Syndecan-4 is a widely expressed transmembrane heparan sulfate proteoglycan which localizes to focal adhesions. Previous studies showed that the syndecan-4 cytoplasmic domain can associate with and potentiate the activity of protein kinase C, which is required for focal adhesion formation. To examine further the role of syndecan-4 in cell adhesion, we expressed syndecan-4 cDNA constructs in CHO-K1 cells. Syndecan-2 transfection was used to confirm effects seen were specific for syndecan-4. Cells overexpressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…In fibronectin, the RGD sequence is located in a short loop that extends from the tenth type III repeat (FNIII10) where it mediates adhesion for a variety of cell types, including epithelial cells, endothelial cells and fibroblasts, via β 1 and β 3 integrins (23,24). Ligation of cell surface integrins with the RGD sequence of fibronectin triggers a cascade of cell signaling events, including protein kinase C activation and Rho-mediated actomyosin contractility, that lead to changes in cell shape (25), focal adhesion composition (26,27), and extracellular matrix assembly (28). Critically, activation of components of these adhesion-based signaling cascades has been associated with reduced endothelial and epithelial barrier function and increased prevalence of inflammatory diseases (29).…”
Section: Introductionmentioning
confidence: 99%
“…In fibronectin, the RGD sequence is located in a short loop that extends from the tenth type III repeat (FNIII10) where it mediates adhesion for a variety of cell types, including epithelial cells, endothelial cells and fibroblasts, via β 1 and β 3 integrins (23,24). Ligation of cell surface integrins with the RGD sequence of fibronectin triggers a cascade of cell signaling events, including protein kinase C activation and Rho-mediated actomyosin contractility, that lead to changes in cell shape (25), focal adhesion composition (26,27), and extracellular matrix assembly (28). Critically, activation of components of these adhesion-based signaling cascades has been associated with reduced endothelial and epithelial barrier function and increased prevalence of inflammatory diseases (29).…”
Section: Introductionmentioning
confidence: 99%
“…Distinct studies have already reported a significance of syndecans expression in normal cell functioning and also in alterations linked with different diseases, including cancers . Syndecan-1 (SDC1) is largely expressed in mesenchymal and epithelial cells, syndecan-2 is predominant in mesenchymal, neuronal, and epithelial cells, syndecan-3 is almost exclusively characteristic for neuronal and musculoskeletal tissues, while syndecan-4 (SDC4) is common for a wide variety of cell types. , SDC1 shows the highest expression on epithelial cells such as keratinocytes and terminally differentiated cells such as plasma cells. It plays an important role in regulation of inflammation (as suggested by increased leukocyte–endothelial interactions in knockout mice) or in chemokine gradient formation for trans-endothelial and trans-epithelial migrations of neutrophils. , SDC4 is mainly associated with cellular adhesion and migration. , It occurs alongside integrins within the focal adhesions to which ECM proteins bind. , In syndecan-4-deficient mice, an absence of SDC4 causes low prevention of mice to endotoxin shock and impairments in wound healing . Syndecans facilitate interactions of integrins with ECM. SDC4 is frequently associated with β 1 and β 3 integrins in focal adhesions. SDC1 interacts with α v β 3 integrin associated with vitronectin and also with α v β 5 integrin that binds to matrix macromolecules and proteinases and thereby stimulates angiogenesis …”
mentioning
confidence: 99%
“…11,12 SDC4 is mainly associated with cellular adhesion and migration. 13,14 It occurs alongside integrins within the focal adhesions to which ECM proteins bind. 15,16 In syndecan-4-deficient mice, an absence of SDC4 causes low prevention of mice to endotoxin shock 17 and impairments in wound healing.…”
mentioning
confidence: 99%
“…For example, wound healing is delayed in syndecan 1-null mice (Stepp et al, 2002), and over-expressing syndecan 1 in mice also leads to delayed wound healing with defective granulation tissue angiogenesis (Elenius et al, 2004). Similar observations have also been made for syndecan 4 in wound closure (Longley et al, 1999;Echtermeyer et al, 2001) and myocardial infarction (Matsui et al, 2011). Further work is therefore required to determine the effects of manipulating syndecan expression in disease.…”
Section: (Iv) Roles Of Syndecans In Osteogenesismentioning
confidence: 68%